Perlindungan Hukum terhadap Pembeli yang Beritikad Baik terkait Jual Beli Tanah Dan Implikasinya: Studi Kasus Putusan Mahkamah Agung, Nomor: 2943/K/Pdt/2016 - Pandji Pratama; Maman Suparman (Sekolah Tinggi Ilmu Hukum Prof Gayus Lumbuun, 2025)
Buying and selling issues cannot be separated from people's daily lives and good faith in buying and selling is an important factor so that buyers who have good intentions will receive reasonable legal protection according to applicable laws and regulations. Good faith in buying and selling is closely related to buying and selling land, because in national development the role of land is very important. So a problem arises, what is the position of buyers who have good intentions in buying and selling land carried out by PT. JASA MARGA (Persero) and what is the position of the holder of land rights obtained by a legal entity. In this research, normative juridical research methods were used. Position of PT. JASA MARGA (Persero) in the sale and purchase of a plot of land based on SHM No. 3147 in the name of Dewi Astuti, namely as a buyer in good faith. Even though in the sale and purchase the object being traded was legally defective because the certificate was issued based on a fake document which resulted in the objective conditions of an agreement not being fulfilled. But because PT. JASA MARGA (Persero) has been proven to be a buyer in good faith, therefore must receive legal protection based on applicable laws and regulations. Legal consequences for ownership of land rights obtained by PT. JASA MARGA (Persero) based on the transfer of rights between Dewi Astuti and PT. JASA MARGA (Persero) is invalid. Because PT. JASA MARGA (Persero) as a legal entity cannot have ownership of land rights in the form of property rights. Legal entities can only control land with a right, a right as in Article 30, Article 36 and Article 42 of UUPA Number 5 of 1960, namely Business Use Rights, Building Use Rights and Use Rights